Assessment of e-learning Experience of Senior High School Students in a Private School - Jeff B. Sagala; Ismael A. Haguisan III; Rhon Dave P. Suarez (Philippine Social Science Journal, 2022)
The global pandemic drastically impacted the education landscape, directing schools to shift from traditional classrooms to online education. Online education paved the way for e-learning as the new normal mode of education. This study assessed the e-learning experiences of Senior High School students in a private academic institution that used a descriptive-correlational research design using mean, standard deviation, t-test, ANOVA, and Pearson correlation coefficient in data analysis. Three hundred sixteen students were surveyed. Results showed that perceived quality is very positive, and students were highly satisfied with their e-learning experience; however, this was not translated to the behavioral intention of recommending e-learning to other students. Results also showed that only the perceived quality significantly differs while the other dimensions do not vary. Finally, the results showed that e-Learning quality, level of satisfaction, behavioral intention, and grade expectation were all positively correlated. It can be concluded that students show a positive assessment of their e-learning experience. However, developing strategies that will enhance their educational learning experience is still recommended to fully embrace the new normal education.